2012
DOI: 10.1111/j.1526-4637.2012.01439.x
|View full text |Cite
|
Sign up to set email alerts
|

Denial of Prescription Opioids Among Young Adults with Histories of Opioid Misuse

Abstract: Objectives An exploratory study was undertaken to examine how being denied prescription opioids to treat pain impacted the drug-using careers of young adults with a history of misuse of prescription drugs. Design Ethno-epidemiological methodology utilizing a cross-sectional design, semi-structured interviews, and qualitative/quantitative data analysis. Settings Non-clinical participants were recruited from natural settings, such as streets, parks, beaches, and college campuses, in New York City and Los Ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…We also included three variables that were described as important correlates of NMUPO use in non-LCA studies (Nielsen et al, 2011; Fibbi et al, 2012; Wang et al, 2013): Metropolitan Statistical Area (large metropolitan area, small metropolitan area, and non-metropolitan area); health insurance (yes or no); and employment status (employed, unemployed, and missing).…”
Section: Methodsmentioning
confidence: 99%
“…We also included three variables that were described as important correlates of NMUPO use in non-LCA studies (Nielsen et al, 2011; Fibbi et al, 2012; Wang et al, 2013): Metropolitan Statistical Area (large metropolitan area, small metropolitan area, and non-metropolitan area); health insurance (yes or no); and employment status (employed, unemployed, and missing).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, many participants (44%) reported that prescription analgesia denial was commonly related to “being accused of drug seeking” (Voon et al, 2015a). Similarly, in a study of young adults who engaged in non-medical use of an opioid, tranquilizer and/or stimulant in the last 90 days, participants associated their experiences with being denied prescription analgesia with being identified as a drug user, a lack of health insurance, and having medication withheld by a parent or authority figure (Fibbi et al, 2012). Approximately 40% of young adults in this sample who did not receive treatment escalated their NMPO use or self-medicated with heroin.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports suggest that misidentification of risk factors for and symptoms of OUD, as well as complexities associated with managing patients who are concurrently experiencing physical pain and receiving treatment for opioid addiction could increase some clinicians’ reticence to prescribe opioid medications (Rupp and Delaney, 2004; Fibbi et al, 2012; Dowden, 2014; King, 2014; Rutkow et al, 2015; Voon et al, 2015a). The high prevalence of untreated physical pain among patients who display symptoms of OUD, which has been shown to range in samples of individuals seeking methadone treatment from 37% to 61%, may also be related to frequent co-occurrence of other substance use disorders and mental health disorders (Jamison et al, 2000; Rosenblum et al, 2003; Savage et al, 2008; Pettes et al, 2015; Voon et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations